2009
DOI: 10.1111/j.1540-5893.2009.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Legal Consciousness and Responses to Sexual Harassment

Abstract: Studies of legal mobilization often focus on people who have perceived some wrong, but rarely consider the process that selects them into the pool of potential "mobilizers." Similarly, studies of victimization or targeting rarely go on to consider what people do about the wrong, or why some targets come forward and others remain silent. We here integrate sociolegal, feminist, and criminological theories in a conceptual model that treats experiencing sexual harassment and mobilizing in response to it as interre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 46 publications
2
58
0
2
Order By: Relevance
“…This process is partly a function of legal consciousness – individuals’ awareness, understanding, and response to law and legality (see, e.g., Ewick and Silbey 1998; Blackstone, Uggen, and McLaughlin 2009; Hirsch and Lyons 2010). Authority position and other independent variables are likely tied to both legal consciousness and sexual harassment.…”
Section: Data Measures and Methodologymentioning
confidence: 99%
“…This process is partly a function of legal consciousness – individuals’ awareness, understanding, and response to law and legality (see, e.g., Ewick and Silbey 1998; Blackstone, Uggen, and McLaughlin 2009; Hirsch and Lyons 2010). Authority position and other independent variables are likely tied to both legal consciousness and sexual harassment.…”
Section: Data Measures and Methodologymentioning
confidence: 99%
“…Nevertheless, a number of theoretical perspectives have been influential in guiding SH research. Covered here are: the natural‐biological model; sociocultural explanations which focus on the ways in which harassment stands as a manifestation of a wider system of asymmetrical power relations between men and women (Thomas 1997); theories of legal consciousness which address how perceptions of SH are shaped and the likelihood of subsequent responses (Blackstone et al . 2009); and organizational perspectives which ascribe the incidence and form of SH to particular workplace contexts (Blackstone et al .…”
Section: How and Why Sh Occursmentioning
confidence: 99%
“…Theories of legal consciousness address how perceptions of SH are shaped and the likelihood of subsequent responses (Blackstone et al . 2009).…”
Section: How and Why Sh Occursmentioning
confidence: 99%
“…One area that has received a lot of attention is consumer problems, both by legal scholars and by researchers interested in consumer behavior more generally (Warland et al 1975, Best and R.Andreasenn 1977, Day and Hunt 1978, Best 1981, Ladinsky and Susmilch 1985, Office of Fair Trading 1986, Vidmar 1988; in fact for those working in the latter tradition there is a specialized journal, Journal of Consumer Satisfaction, Dissatisfaction & Complaining Behavior, published now on an annual basis. 4 Two related areas that have received significant attention from scholars are discrimination (Bumiller 1987, Bumiller 1988, Kritzer et al 1991b, Hirsh and Kornrich 2008 and sexual harassment (Quinn 2000, Marshall 2003, Marshall 2005 Oñati Socio-Legal Series, v. 1, n. 6 (2011) ISSN: 2079-5971 7 Blackstone et al 2009). One other area where there has been at least one study looking at the decisions of grievants to seek redress is medical negligence (May and Stengel 1990).…”
Section: Dispute Processingmentioning
confidence: 99%
“…Oñati Socio-Legal Series, v. 1, n. 6 (2011) ISSN: 2079-5971 16 sexual harassment, Blackstone et al (2009) included a measure for personal efficacy (a person's belief about his or her own ability to obtain a desired result), but found that it had no relationship with seeking redress. The most extensive examination of psychological factors was done by Vidmar and Schuller (1987) who report a series of four studies examining "claim propensity," which they measured as a combination of six components: aggressiveness, competitiveness, assertiveness, perceptions of control, preference for risk, and preference for winning over compromise.…”
mentioning
confidence: 99%